1995
DOI: 10.2337/diacare.18.2.245
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Areas Under Curves in Diabetes Research

Abstract: Recently, several articles appearing in the diabetes literature have suggested that many investigators are unclear about a number of issues involving the use of areas under the curve (AUCs). This prompted us to reconsider issues in the calculation, use, meaning, and presentation of AUCs. We discuss five issues: 1) What is a curve and an area? 2) How should one graphically present a group's curve? 3) How should one calculate AUCs? 4) Should one subtract baseline values from outcome values before calculating AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
263
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(265 citation statements)
references
References 14 publications
0
263
0
2
Order By: Relevance
“…As recently pointed out by Allison et al, 1 interpretation of glucose and insulin data are subject to limitations of analysis depending upon which method is used to calculate the AUC. The main finding of this investigation is that following 9 months of exercise the incremental and positive incremental methods for calculating insulin AUC will result in an inter- Areas under the curve JA Potteiger et al pretation of no change in AUC, while employing the total AUC method would suggest an improvement for insulin action following 9 months of aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently pointed out by Allison et al, 1 interpretation of glucose and insulin data are subject to limitations of analysis depending upon which method is used to calculate the AUC. The main finding of this investigation is that following 9 months of exercise the incremental and positive incremental methods for calculating insulin AUC will result in an inter- Areas under the curve JA Potteiger et al pretation of no change in AUC, while employing the total AUC method would suggest an improvement for insulin action following 9 months of aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In one method the baseline measures are subtracted from all subsequent readings before the AUC is calculated and is referred to as the 'incremental area' method. 1 A major problem exists when using this method, 'if any of the postbaseline measures are lower than the baseline value, then it is possible to obtain a negative area, and a negative value for area logically contradicts the concept of area in the physical sense.' Another method for determining the AUC is to use only those areas that are above the baseline values and ignore any value that falls below baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Measured C-peptide values are non-zero and simulation studies suggested that integrals estimated from trapezoidal rule outperformed all other methods when functions are non-zero [17]. The 'minus 10' minute and 'zero' minute measure for C-peptide level was averaged to obtain the pre-meal baseline level of C-peptide and the subsequent measures were used to calculate total AUC for each participant.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC was calculated according to the trapezoidal model (Bryant, 1983;Allison et al, 1995). Incremental areas of the curve from baseline (fasting) values over time were calculated up to 90, 120, and 240 min after the meal.…”
Section: Statistical Analysis Data Are Presented As Means7standard Dementioning
confidence: 99%